Well differentiated fetal adenocarcinoma of the lung in a 29 year old woman. Issue 6 (1st June 2003) - Sheehan, K M; Curran, J; Kay, E W; Broe, P; Grace, A
Abstract : This report describes a case of well differentiated fetal adenocarcinoma of the lung in a 29 year old female smoker. The histological pattern and immunohistochemical profile were consistent with well differentiated fetal adenocarcinoma and the patient made an uneventful postoperative recovery with no recurrence after 18 months. This neoplasm is a rare lung tumour that is composed of glycogen rich neoplastic glands and tubules that resembles fetal lung at 10 to 15 weeks of gestation. It is important to identify this rare variant of adenocarcinoma because it is a low grade malignancy with low associated mortality.